Tired of Being a Refugee - Fiorella Larissa Erni (Graduate Institute Publications, 2013)
After six decades of protracted refugeehood, patterns of social identification are changing among the young people of the fourth refugee generation in the Palestinian refugee camp Burj al-Shamali in Southern Lebanon. Though their identity as Palestinian refugees remains the same compared to older refugee generations, there is an important shift in the young refugees' relationship towards the homeland, their status as refugees, Islam, the camp society, as well as in their relationship towards ...